A geographic information system (GIS) assisted modelling technique in the estimation of soil moisture in the Angat watershed - Roa, Melo Jane D. (1997)
Soil moisture content in the Angat watershed was measured through point sampling using an ordinary hand auger. The information obtained from the nine sampling points using the point measurement did not fully depict the distribution of the available soil-water content over the entire area. The distribution of moisture over large areas was proposed to be estimated by modelling the different parameters. Mathematical modelling was achieved through correlation and regression analyses of several dependent and independent variables. There were ten independent variables included in the study. These were composed of the soil properties, climatic, topographic, and land surface parameters. The actual soil moisture content obtained through point measurement was identified as the dependent variable. The measurement of these variables were obtained from two seasons (wet and dry) and two soil depths (0-15 cm. and 15-3- cm.) Pearson's correlation analysis using the SPSS version 6.0 was used to determine the relationships of each of the variables. Stepwise linear regression procedures using a confidence level of 90% or a = 0.10 was applied to form a regression equation. As an important aspects in regression analysis, hypothesis testing was employed to determine the relationship between variables. This was achieved through the combination of the graphical analyses and statistical tests. The results of the analyses lead to the derivation of the models. Possible model candidates were evaluated using statistical measures to determine the goodness-of-fit of the regression model equation. Considering two different seasons and soil depths, four models were proposed in estimating the soil moisture content in the Angat watershed. Out of the four proposed models, three appeared to be acceptable for estimating the amount of water content in Angat while one model was determined to have violated the assumptions of a good model and was therefore excluded. The results of the mathematical models were used to determined the spatial distribution of soil moisture content in the Angat watershed for each land cover type from different seasons and soil depths. Translation into graphical forms was done using the GIS technique. Maps were created using a combination of the PC-based ARC/INFO, workstation-based ARC/INFO and ArcView softwares. Soil moisture distribution maps at two seasons and two soil depths were obtained using GIS which can be used for decision making processes and as input for hydrological studies.